2017
DOI: 10.1007/s00330-017-5069-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative reliability and diagnostic performance of conventional 3T magnetic resonance imaging and 1.5T magnetic resonance arthrography for the evaluation of internal derangement of the hip

Abstract: ObjectiveTo compare the diagnostic accuracy of conventional 3T MRI against 1.5T MR arthrography (MRA) in patients with clinical femoroacetabular impingement (FAI).MethodsSixty-eight consecutive patients with clinical FAI underwent both 1.5T MRA and 3T MRI. Imaging was prospectively analysed by two musculoskeletal radiologists, blinded to patient outcomes and scored for internal derangement including labral and cartilage abnormality. Interobserver variation was assessed by kappa analysis. Thirty-nine patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…However, although several studies have reported a higher accuracy for MR arthrography in the detection of chondrolabral lesions [17,30,31], the use of intraarticular contrast might not be logistically feasible in a larger study trial and/or in clinical [32], and, more importantly, for the majority of these studies, a 1.5-T MRI system was used. In this context, recent studies have shown that the use of a high-resolution, nonarthrographic 3-T MRI is capable of detecting chondral and labral abnormalities with high accuracy [20,33,34] and therefore may obviate the need for intraarticular contrast. One of the primary characteristics of our study design was the feasibility of SHOMRI to detect cartilage lesions with surgical reports as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, although several studies have reported a higher accuracy for MR arthrography in the detection of chondrolabral lesions [17,30,31], the use of intraarticular contrast might not be logistically feasible in a larger study trial and/or in clinical [32], and, more importantly, for the majority of these studies, a 1.5-T MRI system was used. In this context, recent studies have shown that the use of a high-resolution, nonarthrographic 3-T MRI is capable of detecting chondral and labral abnormalities with high accuracy [20,33,34] and therefore may obviate the need for intraarticular contrast. One of the primary characteristics of our study design was the feasibility of SHOMRI to detect cartilage lesions with surgical reports as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast extending into the labrum or its base facilitates the diagnosis of labrum tears, and contrast accumulation between the femoroacetabular interface indicates cartilage thinning or defects. Encouraging results of two recent studies suggested that due to its higher SNR, noncontrast MRI at 3 T could replace direct MR arthrography at 1.5 T. 108,109 In contrast, a higher diagnostic performance was reported for direct MR arthrography at 1.5 and 3 T in other studies. [110][111][112] In light of these conflicting reports, it is important to highlight that extensive cartilage damage (> 2 hours on the clock face, i.e., extending over 60 degrees on the radial plane) was identified as the strongest risk factor for long-term failure of FAI correction based on preoperative direct MR arthrography at 1.5 T that supports its prognostic value.…”
Section: Mri Protocolmentioning
confidence: 99%
“… 5 , 6 Although promising results have been demonstrated for non-contrast MRI of the hip at 3 T, direct MR arthrography is still the current diagnostic gold-standard in the detection of chondrolabral lesions. 7 9 MR arthrograms provide crucial prognostic information as extensive cartilage defects, acetabular cysts and osteophyte formations indicate a higher risk for failure of femoro-acetabular impingement (FAI) surgery in the long-term. 10 Injection of intra-articular contrast agent further enables application of leg traction to achieve joint distraction and has shown promising early results to improve the visualization of intra-articular lesions.…”
Section: Pre-operative Workupmentioning
confidence: 99%